Legal And Economic Problems Due To The Prohibition Indian Rice Imports To Indonesia - Chandra, Ade; Firmanto, Aditia Arief; Subekti, Ade Ryan; Pratama, Bagas Maulana; Saputri, Bela; Hasanah, Chairani Anugrah; Puspita, Dea; Futri, Della Monica; Helpira, Deswita; Julita, Dewi (Universitas Malayati, 2024)
The Indonesian government introduced rice import activities as a necessary requirement to increase national rice reserves. In Indonesia, policies regarding the export and import of rice have been regulated in the Regulation of the Minister of Trade of the Republic of Indonesia Number 1 of 2018 concerning provisions for the export and import of rice. Rice imports are carried out by the Public Logistics Affairs Agency (Perum Bulog). The problem from a legal and economic point of view is that the policy of banning Indian rice exports will affect the reduced supply of rice reserves in Indonesia, due to the reduced supply of rice in Indonesia, inevitably the Indonesian government will make a policy by increasing the price of rice sold in Indonesia. The ban on Indian rice imports to Indonesia certainly did not just happen. According to the data the author obtained, India's export ban policy to other countries was motivated by monsoon rains which resulted in a decrease in rice yields in India. In this study the authors used normative juridical legal research methods or library research. For the Indonesian government to immediately look for other rice supplying countries to cover the shortage of rice in Indonesia, so that the people are not increasingly suffocated by the increase and scarcity of rice prices due to the ban on imports of Indian rice to Indonesia.